What happens when crops are turned on? Simulating constitutive volatiles for tritrophic pest suppression across an agricultural landscape. Issue 1 (30th April 2014) - Kaplan, Ian; Lewis, Danny
Abstract BACKGROUND Herbivore‐induced plant volatiles, or HIPVs, are increasingly considered as a biocontrol enhancement tool by constitutively emitting these carnivore‐attracting chemicals from agricultural fields. While ample data substantiate the olfactory preference of predators for HIPVs in laboratory environments, little is understood about the consequences of 'turning crops on' in the field. To explore the ramifications for arthropod pest management, a spatially explicit predator–prey population model was constructed that simulated a crop field releasing signals to recruit natural enemies from the surrounding landscape. RESULTS Field size had an overriding influence on model outcome, both isolated as a single factor and interactively shaping responses to other parameters (e.g. habituation, foraging efficiency). Predator recruitment exponentially declined with increasing field size from nearly double the baseline density in small fields (225 individuals m−2) to a mere 4% increase (130 individuals m−2) in large fields. Correspondingly, HIPVs enhanced pest consumption in small fields (ca 50% fewer prey), while generating virtually no impact in large fields. CONCLUSION Collectively, the model suggests that reducing the perimeter/core area ratio will ultimately constrain the utility of predator retention as a pest control tactic in commercial‐sized fields and illustrates potential consequences of the widespread commercialization of this technology in agriculture. © 2014 Society of Chemical Industry